Evaluation of resveratrol-doped adhesive with advanced dentin bond durability. (November 2021) - Guo, Rui; Peng, Wenan; Yang, Hongye; Yao, Chenmin; Yu, Jian; Huang, Cui
Abstract: Objectives: This paper aimed to evaluate the influence of resveratrol-doped adhesive on the durability and antibiofilm capability of dentin bonding. Methods: Experimental adhesives were prepared by incorporating resveratrol into a universal adhesive at concentrations of 0 (control), 0.1, 1, and 10 mg/mL. The microtensile bond strength, fracture modes, and adhesive–dentin interface nanoleakage were assessed after 24 h of water storage, 10, 000 times of thermocycling or 1-month of collagenase ageing. Relevant antibiofilm capability on Streptococcus mutans ( S. mutans ), in situ zymography, degree of conversion, and cytotoxicity of resveratrol-doped adhesives were also determined. Results: Irrespective of thermocycled or collagenase ageing, the resveratrol-doped adhesive (1 mg/mL) maintained the bond strength and reduced the nanoleakage expression. Meanwhile, the inhibitory ability on endogenous protease activity and S. mutans biofilm formation with acceptable biocompatibility were obtained. Conclusions: This study suggested that the resveratrol-doped adhesive achieved effective improvement on dentin bond durability and secondary caries management. Clinical significance: The application of the resveratrol-doped adhesive indicates promising benefits to increase the lifetime of composite restorations.